Green tea extract prevents the development of nonalcoholic liver steatosis in rats fed a high-fat diet - Karolczak, Dominika; Seget, Monika; Bajerska, Joanna; Błaszczyk, Agata; Drzymała-Czyż, Sławomira; Walkowiak, Jarosław; Marszałek, Andrzej (Polish Journal of Pathology, 2019)
Green tea contains many polyphenolic constitutes, which might prevent non-alcoholic fatty liver disease (NAFLD). We aimed to investigate whether green tea extract (GTE) given at doses reflecting habitual consumption of green tea beverages prevents development of NAFLD in rats fed a high-fat diet (HFD). Twenty-four male Wistar rats were randomly divided into four equal groups (two study and two control groups). The study groups received a HFD (approximately 50% energy from fat), enriched with 1.1% and 2.0% GTE, respectively, for a total of 56 days. The control groups were fed a HFD alone and normal standardised diet (low-fat diet), respectively, for the same period of time. The percentage of hepatocytes affected by steatosis in the HFD group (median [1st-3rd quartile]: 25% [12-34%]) was higher (p < 0.033 and p < 0.050, respectively) than in the HFD-2.0%GTE group (9% [3-18%]) and normal diet group (10% [5-18%]). No significant differences were observed for the group consuming HFD-1.1%GTE, in which intermediate results were observed (15% [4-30%]). This finding points towards the hepatoprotective potential of GTE in preventing dietary-induced liver steatosis. In view of the increasing incidence of overweight and obesity a simple and cheap dietary modification, such as GTE supplementation, could prove to be useful clinically.